Gender Innovation in Political Science
XVII, 285 p. 11 illus.
Keywords: In this book, leading gender scholars survey the contribution of feminist scholarship to new norms and knowledge in diverse areas of political science and related political practice. They provide new evidence of the breadth of this contribution and its policy impact. Rather than offering another account of the problem of gender inequality in the discipline, the book focuses on the positive contribution of gender innovation. It highlights in a systematic and in-depth way how gender innovation has contributed to sharpening the conceptual tools available in different subfields, including international relations and public policy. At the same time, the authors show the limits of impact in core areas of an increasingly pluralised discipline. This volume will appeal to scholars and students of political science and international relations.